The banality of Being and Becoming - Papagiannis, Lampros (Dia-noesis: A Journal of Philosophy, 2024)
Throughout the history of philosophy there seems to be a distinction between or among schools of thought. For instance, idealism and materialism or behaviourism and natural predisposition. This article deals with the distinction between Being and Becoming demonstrating not only its importance, but also its internationality, as it appears that the distinction between Being and Becoming, which often takes the form of rivalry, does not concern Western philosophy alone, but it can be found, though under different forms, in the East, too. Several examples will show that, one way or another, the differentiation between the unborn, undead, perfect Being and the everlasting, never-ending Becoming go beyond the rivalry between the Monists (Parmenides, Zeno, Melissus) and Heraclitus. Please be advised that this article will only try to present this matter based on specific examples from the history of philosophy from Greece, India, and China. As it becomes understandable such a matter can (or should) be dealt with in a much larger scale, perhaps as the topic of a doctoral thesis.